2001
DOI: 10.1063/1.1369618
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscope-induced modification of Ag films and nanowire arrays on Cu(100) surfaces

Abstract: We demonstrate the ability to use scanning tunneling microscopy to create nanometer-scale pits on Ag films grown on Cu(100) substrates. Atomic resolution images show that the Ag structures are intact within these pits. We also demonstrate how we can selectively modify segments of Ag nanowire arrays grown on atomic nitrogen modified Cu(100) surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Also the early growth (up to 2 ML) of Ag on N modified Cu(001) was reported in the past by STM [1,33]. It was shown [34] that the growth of Ag in this case proceeds in the same guise as on the clean Cu(001) surface, i.e., with a c(2x10) periodicity for the first layer of Ag growing on clean Cu and forming an unreconstructed Ag(111) layer for Ag stripes of higher thickness. In this paper we consider much higher coverage values than previously reported and the whole sequence of Ag overlayers is here discussed.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Also the early growth (up to 2 ML) of Ag on N modified Cu(001) was reported in the past by STM [1,33]. It was shown [34] that the growth of Ag in this case proceeds in the same guise as on the clean Cu(001) surface, i.e., with a c(2x10) periodicity for the first layer of Ag growing on clean Cu and forming an unreconstructed Ag(111) layer for Ag stripes of higher thickness. In this paper we consider much higher coverage values than previously reported and the whole sequence of Ag overlayers is here discussed.…”
Section: Resultsmentioning
confidence: 54%
“…2c) we cannot give evidence of this process. At higher thickness the Ag overlayer grows as unreconstructed Ag(111) [34,46]. Also the early growth (up to 2 ML) of Ag on N modified Cu(001) was reported in the past by STM [1,33].…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…[23][24][25] The STM study of Sprunger et al 23 concluded that at subsaturation coverages Ag forms a layer-confined surface alloy even at temperatures as low as 300 K. It was found that only ϳ0.13 ML of Ag can be alloyed into the Cu͑100͒ surface. At higher Ag coverages, pseudohexagonal c͑10ϫ 2͒-Ag patches condense within the Cu͑100͒ surface layer.…”
Section: Introductionmentioning
confidence: 97%